Effects of Demographic and Organizational Factors on Job Satisfaction of Employees in Human Resource Shared Service Center (HR SSC) in Intel Malaysia - Selve, Krishnan (2010)
This study explores and describes the impact of age, gender, job level and salary on job satisfaction among Human Resource Shared Service Center employees in Intel Malaysia. This is based on Herzberg's motivation hygiene theory which provides the framework to extend research in the context of a big organization lacking published information on the current levels of job satisfaction in the organization. Data from 136 participants are being collected. Findings are discussed and analyzed. This study will help to understand the needs of employees and what changes could improve the work environment that may assist managers and leaders in developing a more productive workplace.